Dampak Ekonomi Politik Media Terhadap Agenda Setting Pemilu Di Indonesia - Ardila, Putri; Abrar, Darell Abhirama; Juniati, Deby Nurul (Tuturlogi: Journal of Southeast Asian Communication, 2024)
The mass media plays an important role in election agenda setting, where they determine the issues that are considered important and discussed by the public. This research aims to analyze how the political economy of the media influences the election agenda setting in Indonesia. This research uses qualitative methods with case studies in national mass media during the 2024 Presidential Election campaign. Data was collected through media content analysis and interviews with sources from mass media, academics and social movement activists. The research results show that the political economy of the media has a significant influence on the election agenda setting in Indonesia. The mass media tends to give a larger share of news to candidates and political parties with strong economic and political power. This research also found that the mass media often ignores issues that are important to society at large, such as poverty, social inequality and environmental damage. This happens because the mass media is more interested in reporting sensational issues and attracting public attention. This research recommends the need for stricter media regulations to prevent media bias in election agenda setting. The public also needs to increase media literacy so that they are not easily influenced by media framing.